Development of an online animated sexting prevention module based on the prototype willingness model to reduce intention and willingness to sexting among diploma students - Mansor, Norain; Ahmad, Norliza; Md Said, Salmiah; Tan, Kit-Aun; Sutan, Rosnah (Malaysian Medical Association, 2023)
Introduction: Sexting refers to the act of sending and receiving sexually explicit content in the form of in the form of texts, photos, or videos via the Internet and mobile phones. This behaviour is associated with many negative health consequences among young people. However, there is a lack of intervention studies to curb this behaviour. We have developed a new sexting prevention module and tested it using a randomised controlled field trial. This paper reported the phase one of the study i.e., the development of an animated sexting prevention module using the prototype willingness model (PWM) to reduce the intention and willingness to sext amongst diploma students in Malaysia. Materials and Method: The initial phase involved a review of previous interventions, validation from field experts, and the process of developing video. Then the module pilot was tested among 30 diploma students from a public university. They were given access to the newly developed videos posted on a private YouTube channel and asked to evaluate the videos quantitatively and qualitatively by using the acceptability of the intervention module (AIM), intervention appropriateness measure (IAM) and feasibility of the intervention measure (FIM). The minimum and maximum scores of each measure were 12 and 24 respectively whereby a higher score indicated greater acceptability, appropriateness and feasibility. Results: The intervention consisted of five sections addressing the constructs of PWM, namely attitude, perceived norm, prototype perception, as well as intention and willingness of sexting. The contents were then converted into five videos with a total duration of 23 minutes. Based on the pilot test, the scores of AIM, IAM and FIM were not normally distributed and their median and the interquartile range values were 20 (4), 21 (4) and 22 (4) respectively. Most of the respondents gave favourable opinions on the intervention besides providing some input for improvement. Conclusion: This animated sexting intervention module based on PWM to reduce the intention and willingness was novel. The module was acceptable, appropriate and feasible to be implemented among undergraduate students. Further evaluation of this intervention module can be performed to provide more comprehensive evidence of its effectiveness.